Stroke parameter analysis during a competition distance (200m) in canoe sprint on an ergometer and on water - Veispals, M.; Gulbe, A. (LASE Journal of Sport Science, 2022)
Canoe sprint is a specific type of sport (under natural conditions, it takes place on water); therefore, a large part of research is carried out under laboratory conditions, when the load is performed on various special exercise machines (ergometers) that try to simulate natural conditions as closely as possible. Thus, one of the fields of research in canoe sprint is the mutual correlation of various indicators - kinematic, physiological and biomechanical - under natural conditions of the sport and under laboratory conditions. Although research have been carried out in the relevant direction, they did not consider specific direct differences in the power of a stroke and stroke parameters when paddling on an ergometer compared to paddling on water. A precise comparison of these differences would provide an opportunity to describe the differences in the characteristics of a full stroke and brace (water phase) when paddling on water and on an ergometer in canoe sprint, simulating a 200m competition distance. The research subject was a European and World championships medallist, - 25 years of age, height - 191.4cm, weight - 99.1kg. In order to obtain stroke parameters during a 200 m competition distance under natural conditions on water and under laboratory conditions while paddling on an ergometer, two experiments were carried out - a field experiment and a laboratory experiment (the two experiments included pulsometry, blood biochemical analysis and dynamometry). There were large percentage differences found among the time parameters of a stroke: when paddling on water, the duration of the unsupported phase was 44.8% shorter (0.08s), and when paddling on an ergometer, the duration of the brace phase was 29.8% longer (0.1s). The total duration of a stroke on water was on average 5% longer (0.02s). This indicates the different nature of the load, as the time in which muscles must be able to perform the maximum transfer of force and power per unit of time is 1/10 longer on water; this, in turn, suggests that coaches need to take these differences into account when preparing athletes; - in athletic training, the parameters of a stroke performed on water should be taken as the basis for the duration of muscle work.